Strategies for the Exploration of Agribusiness Policies and Initiatives for Poverty Reduction in Nigeria - Musa, Umar Farouk; Adam, Musa Umar (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2019)
Agribusiness innovation has contributed to the economic development and industrial capabilities of many countries thereby reducing poverty. However, the potentiality of agriculture in Nigeria has yielded little output due to political and institutional challenges. The cardinal objective of this study is to explore the agribusiness policies and initiatives as a strategy to mitigate poverty in the Nigerian context. Hence, the study employed qualitative research design and collected data from fifteen informants on the strategies to reduce poverty in the study area. Accordingly, findings from the survey indicated that the National, state, Non-governmental organizations, private firms were the main activities applied in pushing agribusiness. Conversely, poor political will, financial constraints, scarcity of agro-allied industries, marketing difficulties, low awareness and enlightenment among the farmers were observed as the major challenges of agribusiness initiatives in Bauchi state. Yet, the results revealed that agricultural revenue, food security, employment opportunities, the involvement of public, private and the NGOs in agribusiness shall accelerate the production of animals and crops. Therefore, the study proposed for steady political commitment from the government through expansion of capital resources in addition to public and private collaboration in agribusiness. The improvement of infrastructural facilities in the state, establishment of marketing boards, and mechanized farming.